Syngeneic lines of chickens. VII. The lines derived from the recombinants at the B complex (MHC) of Rous sarcoma regressor and progressor inbred lines of chickens - Plachý, J; Vilhelmová, M (Folia biologica, 1984)
Based on recombinants between the B haplotypes of chickens of inbred lines CB, CC, and CB.I-B7, three new inbred lines homogeneous in transplantation and erythrocyte antigens were established by backcrossing. These newly established recombinant lines, CB.R1, CC.R1, and CC.R2, together with the original inbred lines, which differ at the B complex (MHC) and in the degree of genetically controlled resistance to progressive growth of RSV-induced tumours, represent a model system for study of the structure of the B complex and of the functions of individual B regions in the control of carcinogenesis.
Keywords: rekombinace genetická; ptačí sarkom; Sarcoma, Avian; hlavní histokompatibilní komplex; Histocompatibility Antigens; genotyp; kur domácí; Animals; Genotype; Major Histocompatibility Complex; Recombination, Genetic; Chickens; zvířata; histokompatibilní antigeny